Soil health assessments: how and why?. Issue 2 (21st March 2019) - Karlen, Douglas L.; Obrycki, John F.
Abstract : The information presented in this article comes from an on‐farm soil health assessment study in central Iowa. Researchers utilized available farm management records to design a sampling strategy that represented the predominant soil map units and provided soil that was analyzed for biological, chemical, and physical indicators of soil health. Earn 1 CEU in Soil & Water Management by reading this article and taking the quiz at www.certifiedcropadviser.org/education/classroom/classes/627 .